Sosialisasi Terhadap Penggunaan Internet Sehat Bagi Masyarakat Kampung Sairo - Risma Petrus; Yuliana Sangka; Mardewi (CV. Multi Kreasi Media, 2024)
The use of the internet now exists in all aspects of people's lives, the internet is here to provide a source of presentation of various types of information and multimedia. The presence of the internet has had a tremendous influence on all levels of society. So through this, it is important to know how to be wise and careful when using the internet. Because there are positive and negative impacts of internet use. The Community Service Team carries the theme of socializing healthy internet use for the people of Sairo village, which is the most important part of providing understanding to the community to be alert in using the internet so that it does not have a bad impact on generations.